Structural basis of fatty acid activation and transport by human FATP2 - Li, Ao; Shi, Junhui; Ma, Dan (浪淘沙预印本平台, 2025)
Fatty acids (FAs) are essential biomolecules that play critical roles in development and growth. Fatty acid transport proteins (FATPs) are responsible for the transport of long-chain FAs (LCFAs) and very-long-chain FAs (VLCFAs), exhibiting bifunctionality that includes both FA transport and acyl-CoA synthetase activity. FATPs are potential drug targets for treating various metabolism-related diseases, including cancers. However, the lack of three-dimensional structures of FATPs has hindered our understanding of their mechanisms. Here, we report a cryo-EM structure of human FATP2 in complex with an acyl-AMP intermediate and an incoming FA substrate at 2.9 Å resolution. The FA substrate, adopting a crescent shape, interacts with the membrane and a reclining membrane-associated helix of FATP2, with its tail half inserted into the membrane and its head half bound to a hydrophobic pocket on FATP2 at the protein-membrane interface. The acyl-AMP is bound below the FA substrate, with the AMP portion in a large central pocket and the acyl group in a hydrophobic tunnel that connects the FA entry pocket and the central pocket. This structure reveals that the FA substrate from the membrane may undergo a two-step translocation process to access the catalytic center. The spacious inner cavity allows the binding of a new FA substrate before the completion of a full reaction cycle, which may be a crucial mechanism to ensure the catalytic and transport efficiency of FATP2. We also demonstrate that FATP2 transport FAs, strictly dependent on the activation of FAs through the acyl-CoA synthetase activity of FATP2. Our findings provide important insights into the catalytic and transport mechanisms of FATPs and offer a structural basis for the development of inhibitors targeting FATPs to treat related diseases.